Effect of annealing dependent blend morphology and dielectric properties on the performance and stability of non-fullerene organic solar cells - Upama, M.; Elumalai, Naveen Kumar; Mahmud, M.; Wright, M.; Wang, D.; Xu, C.; Uddin, A. (Elsevier BV * North-Holland, 2018)
This work demonstrates the influence of annealing temperature on the phase morphology of the polymer-non-fullerene blend and its relationship with the dielectric constants of the blend layer. It is also the first study to report the annealing induced changes in dielectric environment of the active layer blend employing non-fullerene acceptor. Polymer solar cells (PSCs) annealed at 80 °C were found to possess optimal blend morphology favourable for efficient charge separation owing to reduced coulomb capture radius and relatively high dielectric constant, resulting in high power conversion efficiency (PCE) of ~11.4%. The high performing devices fabricated at optimized temperature also exhibited superior charge transport characteristics including high recombination resistance (Rrec) which is 31% higher than the non-annealed devices. The effect of intermolecular aggregation induced by the annealing temperature and its relationship with the disorder states in the blend layer, influencing the electron transport properties is also investigated in detail. Furthermore, a month long degradation study investigating the operational stability of the as-developed non-fullerene based PSCs was also performed and analysed.